Low Serum Magnesium Levels Are Associated With Hemorrhagic Transformation After Mechanical Thrombectomy in Patients With Acute Ischemic Stroke - Qiu, Huijia; Shen, Rui; Chen, Liuwei; Pandey, Sajan; Sun, Jiping; Deng, Haoyu (Frontiers in Neurology, 2022)
Objective: In patients with acute ischemic stroke (AIS), hemorrhagic transformation (HT) is a major complication after mechanical thrombectomy (MT). This study aimed to investigate the relationship between serum magnesium levels and HT after MT Methods: We collected 199 cases of consecutive AIS that received MT due to acute anterior circulation occlusions in our institution between January 2017 and January 2020.. Baseline serum magnesium was obtained from all patients on admission before MT. Patients were divided into two groups based on the occurrence of HT. Univariate and multivariate analyses were performed to investigate whether magnesium was an independent predictor of HT. The receiver operating characteristic (ROC) curve and area under the curve (AUC) were determined. Results: Of the 199 enrolled patients, 40 (20.1%) presented with HT, and 12 (6%) developed symptomatic intracranial hemorrhage (sICH). Patients with HT had lower serum magnesium levels compared to those without HT (0.76 [0.69-0.80] vs. 0.84 [0.80-0.90], p<0.001). The multivariate logistic analysis showed that serum magnesium level (odds ratio, [OR]: 0.000, 95% confidence interval [CI]: 0.000-0.001, p<0.001) was significantly associated with the occurrence of HT. The ROC curve analysis revealed that serum magnesium level could predict HT with an AUC of 0.820 (95% CI: 0.750-0.891 p<0.001). Serum magnesium ≤0.80 mmol/L could predict HT with a sensitivity of 79.2% and a specificity of 70.0%. To be of interest, serum magnesium level wasnt associated with HT when the baseline of serum magnesium was higher than the cut-off value (0.80 mmol/L) in subgroup analysis. Conclusions: Lower baseline serum magnesium levels (<0.80 mmol/L) on admission are associated with increased risk of HT in AIS patients receiving MT.